2020
DOI: 10.18632/aging.103141
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-related miR-574 reduces sperm ATP by targeting ND5 in aging males

Abstract: Couples are delaying childbearing in recent decades. While women experience a notable decrease in oocyte production in their late thirties, the effect of advanced paternal age on reproduction is incompletely understood. Herein, we observed that numerous miRNAs, including miR-574, increased in the sperm of aging males, as indicated by high-throughput sequencing. We demonstrated that miR-574 was upregulated in the sperm of two aging mouse models and was related to inferior sperm motility as an adverse predictor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Accordingly, miRNA content in the seminal plasma significantly changes with age [ 168 ]. By performing high-throughput sequencing of small RNAs in sperm, oocytes and embryos of aged and young mice, it has been demonstrated that there is a differential expression of numerous miRNAs and piRNAs in correlation with the age, most of them involved in embryo development [ 169 ]. A typical example of such a deregulation concerns miR-574, upregulated in the sperm of older mice and significantly related to a decreased sperm motility.…”
Section: Diet Aging and Environmental Pollution Damage Sperm Qualmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, miRNA content in the seminal plasma significantly changes with age [ 168 ]. By performing high-throughput sequencing of small RNAs in sperm, oocytes and embryos of aged and young mice, it has been demonstrated that there is a differential expression of numerous miRNAs and piRNAs in correlation with the age, most of them involved in embryo development [ 169 ]. A typical example of such a deregulation concerns miR-574, upregulated in the sperm of older mice and significantly related to a decreased sperm motility.…”
Section: Diet Aging and Environmental Pollution Damage Sperm Qualmentioning
confidence: 99%
“…A typical example of such a deregulation concerns miR-574, upregulated in the sperm of older mice and significantly related to a decreased sperm motility. Interestingly, miR-574 has been shown to suppress mitochondrial function and ATP production by directly targeting the mt-ND5 gene, a typical mitochondrial gene encoding NADH dehydrogenase 5, an essential component of the complex I [ 169 ].…”
Section: Diet Aging and Environmental Pollution Damage Sperm Qualmentioning
confidence: 99%
“…Excluding differentially expressed miRNAs in oocytes, and overlapping the specific miRNAs in sperm with the differentially expressed miRNAs in embryos, we obtained 33 miRNAs that might contain the contributor of embryo development from the sperm of aging males. Meanwhile, some of these miRNAs were associated with mitochondria, including miR-574, miR-128, let-7b, miR-24, and miR-125a (Ma et al, 2020). In the previous study of our group, we found that miR-574 was upregulated in the sperm of aging males and was related to poor sperm motility as an adverse predictor.…”
Section: Introductionmentioning
confidence: 62%
“…In a previous study of our group, we found that numerous miRNAs, including miR-574 and miR-125a-5p, were increased in the sperm of aging males. Subsequently, we demonstrated that mitochondriarelated miR-574 could suppress mitochondrial function, reduce cellular ATP production by directly targeting mt-ND5 in aging males, and have an adverse effect on early embryonic development (Ma et al, 2020). Moreover, we found that miR-125a-5p, which is highly conserved between humans and mice (Figure S1a), was also upregulated in both sperm and embryos of aging males (Figure 1a), suggesting that it may play a role in the sperm function or embryo development of aging males.…”
Section: Mir-125a-5p Was Upregulated In the Sperm Of Aging Males And Was Related To Poor Sperm Qualitymentioning
confidence: 99%
See 1 more Smart Citation